KELAYAKAN VIDEO DOKUMENTER SUBMATERI STRUKTUR DAN FUNGSI JARINGAN PADA TUMBUHAN DI SMA KELAS XI - Rida, Yuliana Afiana; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aimed to determine the development, including the feasibility of video documentaries on the submaterial structure and function of plant tissue using 4D Thiagarajan, namely define, design, develop, and disseminate. However, this research did not carry out the disseminate stage, only using three stages. The instrument validation questionnaire consists of 3 criteria, namely language, content and filling instructions. The media validation questionnaire consists of 10 aspects with 23 criteria. The feasibility assessment was carried out using a Likert scale. There were 5 validators consisting of 2 lecturers from the Biology Education Study Program, FKIP, Tanjungpura University and 3 Biology teachers from 3 high schools in Pontianak. The results of the data from the validation of the documentary video were analyzed using the Lawshe method. The results of the data from the validation of the documentary video show that the CVI and CVR are more than 1, thus the sub-material documentary video on the structure and function of plant tissue is declared valid or belongs to the category suitable for use.